Lead in bottled waters: contamination from glass and comparison with pristine groundwater - Shotyk, William; Krachler, Michael (Environmental science & technology, 2007)
Using clean lab methods and protocols developed for measuring lead (Pb) in polar snow and ice, we report the abundance of Pb in 125 brands of bottled water from 28 countries. Comparison of six samples of each of three brands of water available in both glass and polyethyelene terephthalate (PET(E)) showed that the waters bottled in glass contained approximately 57, 30, and 26 times more Pb due to leaching from the containers. Excluding the bottled waters in glass, the median Pb concentration in all bottled waters was found to be 8.5 ng/L (n = 185), with a range from <1 to 761 ng/L Pb. Our study includes 25 brands of bottled water from Canada, and the median Pb concentration in these samples was 15.9 ng/L (n = 25), with a range from 2.1 to 268 ng/L. For comparison with the bottled waters, pristine groundwater from six artesian flows in southern Ontario, Canada, where some of the bottled waters originate, yielded a median concentration of 5.1 ng/L Pb (n = 18). The median Pb concentrations reported here for bottled waters from Canada are 32−588 times less than those presented in recently published studies. In fact, all of the waters tested were well below the maximum allowable concentration established by the EU, Health Canada, and the WHO for Pb in drinking water (10 μg/L).
Gesehen am 28.09.2020